(untitled) (Botanica Orientalis: Journal of Plant Science, 2018)
There are numbers of invasive and naturalized alien species in Nepal but studies related to herbivory effects on such species are scarce. An issue of debate is whether invasive alien species get benefited by less herbivory damage in their introduced range. In this study, we investigated the level of herbivory damage in Alnus nepalensis in an area invaded by Ageratina adenophora in Nepal. The damage was compared between invasive A. adenophora and native Alnus nepalensis. Results showed that A. adenophora experienced lower level of leaf damage by herbivores than that of A. nepalensis. This indicated that the invasive A. adenophora might have benefited from reduced herbivory damage behind its successful invasion in Nepalese forest. Further studies are needed to confirm whether controlling of herbivores to lessen the damage in native Alnus nepalensis could enhance its competitive ability against Ageratina adenophora in native vegetation of Nepal. Botanica Orientalis – Journal of Plant Science (2017) 11: 7–11